Investigating the Role of Brainstorming Strategy in the Developing the Writing Skills of First Year Students of the College of Administration and Economics - Jasim, Rafal Mahmood (Journal of Tikrit University for Humanities, 2023)
The present study aims at investigating the role of Brainstorming strategy in developing the writing skills of first year students of the College of Administration and Economics. The population of the study consists of first year students / College of Administration and Economics / University of Mosul. The researcher has intentionally selected (66) first year students, and has prepared an achievement test to check writing skills in the form of (write a paragraph). The instruments used in this research have been divided into the following three phases: 1.Pre-test: it’s purpose is to find out the initial ability of the students before presenting the materials according to the brainstorming method. 2.Treatment: has been given before the students did the post-test. 3.Post-test: it’s purpose is find out students’ development after presenting the materials through the application of the brainstorming method. By using some statistical means to analyze the data, the results show that there has been a statistically significant difference in the mean scores of both the pre- and post-tests in writing skills (in English language) taught according to the brainstorming method.